UNASUR Health: A quiet revolution in health diplomacy in South America. (December 2015) - Herrero, María Belén; Tussie, Diana
Since the creation of Union of South American Nations (UNASUR), health policies became a strategic factor in South America to collectively balance the legacy of neoliberal policies in the region. The aim of this article is first to describe the social, political, and economic processes that explain the emergence of UNASUR and its focus on social policy through healthcare. We then analyze how by virtue of UNASUR's Health Council, healthcare became the spearhead of cooperation giving way to novel forms of diplomacy. In so doing, this article contributes to a broader understanding of the regional health diplomacy and the process of unasurization of health policies as the process of building a new health framework.